Group II metabotropic glutamate receptor interactions with NHERF scaffold proteins: Implications for receptor localization in brain. (14th June 2017) - Ritter-Makinson, Stefanie L.; Paquet, Maryse; Bogenpohl, James W.; Rodin, Rachel E.; Chris Yun, C.; Weinman, Edward J.; Smith, Yoland; Hall, Randy A.
Highlights: NHERF-1 & -2 are novel interacting partners of mGluR2 and mGluR3. NHERF-1 & -2 bind to conserved C-terminal motifs on mGluR2/3. Removal of the PDZ-binding motif enhances mGluR2 signaling. Subcellular localization of mGluR2/3 is altered in NHERF-2 knockout mice. Abstract: The group II metabotropic glutamate receptors mGluR2 and mGluR3 are key modulators of glutamatergic neurotransmission. In order to identify novel Group II metabotropic glutamate receptor (mGluR)-interacting partners, we screened the C-termini of mGluR2 and mGluR3 for interactions with an array of PDZ domains. These screens identified the Na+/H+ exchanger regulatory factors 1 and 2 (NHERF-1 & -2) as candidate interacting partners. Follow-up co-immunoprecipitation studies demonstrated that both mGluR2 and mGluR3 can associate with NHERF-1 and NHERF-2 in a cellular context. Functional studies revealed that disruption of PDZ interactions with mGluR2 enhanced receptor signaling to Akt. However, further studies of mGluR2 and mGluR3 signaling in astrocytes in which NHERF expression was reduced by gene knockout (KO) and/or siRNA knockdown techniques revealed that the observed differences in signaling between WT and mutant mGluR2 were likely not due to disruption of interactions with the NHERF proteins. Electron microscopic analyses revealed that Group II mGluRs were primarily expressed in glia and unmyelinated axons in WT, NHERF-1 and NHERF-2 KO mice, but the relative proportion of labeled axons over glial processes was higher in NHERF-2 KO mice than in controls and NHERF-1 KO mice. Interestingly, our anatomical studies also revealed that loss of either NHERF protein results in ventriculomegaly, which may be related to the high incidence of hydrocephaly that has previously been observed in NHERF-1 KO mice. Together, these studies support a role for NHERF-1 and NHERF-2 in regulating the distribution of Group II mGluRs in the murine brain, while conversely the effects of the mGluR2/3 PDZ-binding motifs on receptor signaling are likely mediated by interactions with other PDZ scaffold proteins beyond the NHERF proteins.